2013 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--22654
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Undergraduate Engineering Education with 3D Virtual Reality Laboratory

Abstract: in new Zealand. She has been working on magnetic shape memory alloys as smart materials and for alternative energy. She has years of experience working on a variety of materials. Her research has been funded by NSF, the Air-Force Office of Scientific Research, NASA, CRDF Global, and industry. Her research projects also benefit society such as her NSF grants where nano-ceramics were used as photocatalysts for cleaning contaminants from water and air or for developing ferromagnetic alloys for alternative energy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It has been shown that for conceptual understanding and education outcomes, remote labs can be a competitive alternative to hands-on laboratories (Madara Ogot, Elliott, and Glumac 2002;M Ogot, Elliott, and Glumac 2003;Nickerson et al 2007;Leung et al 2020). Remote labs can also be used to advertise STEM education amongst high school students, deliver the curriculum to minorities or to students with motion disabilities (Carpenter et al 2017;Ari-Gur et al 2013). Remote labs, on the other hand, separate the instructor from the students, therefore, restricting the students from acquiring essential engineering laboratory skills (Lal et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that for conceptual understanding and education outcomes, remote labs can be a competitive alternative to hands-on laboratories (Madara Ogot, Elliott, and Glumac 2002;M Ogot, Elliott, and Glumac 2003;Nickerson et al 2007;Leung et al 2020). Remote labs can also be used to advertise STEM education amongst high school students, deliver the curriculum to minorities or to students with motion disabilities (Carpenter et al 2017;Ari-Gur et al 2013). Remote labs, on the other hand, separate the instructor from the students, therefore, restricting the students from acquiring essential engineering laboratory skills (Lal et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Work 7: Transforming Undergraduate Engineering Education with 3D Virtual Reality Laboratory [39] Ari-Gur et al presented a set of virtual laboratories made of various educational modules. These virtual labs allow students to simulate, in a 3D environment, experiments related to X-ray diffraction, scanning electron microscopy, heat treatment of various alloyed metals, and different mechanical tests on concrete and asphalt.…”
mentioning
confidence: 99%